Improved Routing Performance in MANET Using Anonymity Algorithm (International Journal of Engineering and Computer Science, 2014)
MANET is a type of wireless ad-hoc network that usually has a routable networking environment. Mobile Ad Hoc Networks use unidentified routing protocols that hide node identities and routes from outside observers to provide anonymity protection. Our existing anonymous routing protocols depending on either hop-by-hop encryption, redundant traffic either produce high cost or it cannot provide privacy protection to data sources, destinations, and routes. We propose a new location based routing protocol which offers high privacy protection at low cost to sources, destinations, and routes. It also has approaches to effectively counter intersection and timing attacks. The proposed plan ensures the privacy of both route and nodes which westudy and simulate the result. This existing protocol achieves better route privacy protection and its lower cost compared to other unidentified routing protocols, and also improving the routing efficiency compared to other geographical routing protocol.